Evaluación de las características físicas y químicas de un bioetanol a partir de frutas tropicales - Cobena Cedeño, Gissela Rocío (2017)
ABSTRAC The objective of this study is focused on obtaining bioethanol from the waste of three tropical fruits through the fermentation of wild yeast applying different percentages of inoculation. An experimental design of Completely Random blocks was applied with factorial arrangement A x B where factor A is equal to the types of fruits (Papaya, Guineo and Pineapple), while factor B is equal to the three levels of yeast Saccharomyces cerevisiae (0 %, 0.50% and 0.10%) with a total of 9 treatments and 2 repetitions, which gives a total of 18 experimental units. The analysis of the data was carried out in the statistical package program STATGRAPHICS, it was established the differences between averages of treatments according to the physical-chemical characteristics of bioethanol, and compared with the Tukey test. To define quality parameters, various analyzes were performed such as: ° brix, pH, turbidity, alcoholic degrees, acidity, density and specific heat; for the validation of the investigation, it underwent a combustion power analysis between a mixture of 10% ethanol and 90% gasoline. The results obtained indicate that the sample (Papaya + 0.05% yeast), showed better chemical and physical characteristics being the best treatment for the production of bioethanol. Keywords: Specific heat; wild yeast; Density, alcoholic, power combustion; ° bri